STRUCTURING ADAPTIVE SELLING DECISIONS: A TCM-ADO-BASED SYSTEMATIC REVIEW AND THE INTRODUCTION OF THE SPIDER FRAMEWORK - Budiman, Dedy (Jurnal Manajemen Bisnis dan Terapan, 2025)
Adaptive Selling Behavior (ASB) has been shown to enhance sales performance significantly; however, the decision-making processes of salespeople need to be more structured in the existing literature. To address this, a systematic literature review (SLR) was conducted, utilizing the Theories, Contexts, and Methods (TCM) as well as the Antecedents, Decisions, and Outcomes (ADO) frameworks, analyzing 41 articles published between 2004 and 2024. The study introduces the SPIDER framework—comprising Strategic Responsiveness, Persuasive Influence, Independent Decision-Making, Dynamic Adaptability, Empathic Understanding, and Resilient Flexibility—as a critical contribution to organizing and measuring decision-making in ASB. This framework bridges theoretical constructs with practical applications, offering clear, measurable guidance for enhancing adaptive strategies in sales. Furthermore, it highlights critical gaps in the literature, particularly regarding the interplay of SPIDER's dimensions and its application in various industrial and cultural contexts. The study outlines a future research agenda focused on validating the SPIDER framework and exploring its potential as a practical tool for developing adaptive sales strategies.